A Sebaran Spasial Karbon Tanah Gunung Marapi - Vivin Auliadesti; Gusnidar Gusnidar; Dian Fiantis (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
[SPATIAL DISTRIBUTION SOIL CARBON MARAPI MOUNTAIN]. Volcanic activity will significantly affect the carbon component and its fraction in the soil. Volcanic soils have high carbon content. This study aimeds to map the soil carbon and its fraction vocanic soil of Mt. Marapi. A total of 93 soil samples were taken with a grid interval of 750 x 750 m at a depth of 0-20 cm spread across the Southwest, West and Northwest areas affected by the eruption of Mt. Marapi at a radius of 4.5-7 km from the peak. The parameters analyzed were: bulk density, soil pH, C-organic, C fractions. The results showed that, soil pH ranged from 4.59-6.19 (pH H2O) and 3.8-5.8 (pH KCl), C organic ranged from 3.00%-14.16%, C-very labile ranged from 0.001-0.045%, C-labile ranged from 0.14-1.41%, C boundts non-crystalline clay ranged from 0.20-2.10%, C-metal complex ranged from 0.11-1.70%. Soil pH in Northwest was different from those of in West and Southwest. Very labile carbon in Southwest slope was not the same as those found in West and Northwest. C-metal complex in Northwest soil did not the same as those found in West and Southwest. The diversity of carbon fractions can be used as a reference in tillage to maintain carbon storage and become a marker for soil health. Full text pdf